2019
DOI: 10.1186/s12906-019-2621-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemical constituents and in vitro antimicrobial, antioxidant and cytotoxicity potential of rhizome of Astilbe rivularis (Bodho-okhati), an indigenous medicinal plant from Eastern Himalayan region of India

Abstract: Background Astilbe rivularis L. is an indigenous medicinal plant growing in high altitude of Darjeeling Himalayan region of India and Nepal. The plant rhizome has been used traditionally as medicine by local tribes to treat various ailments including infectious and other diseases. The present study aims to evaluate the plant rhizome for chemical composition and in vitro antioxidant, antibacterial and cytotoxic bioactivities. Methods The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…C-O stretching and aldehyde group respectively [50]. Similar results were previously reported by [51] which revealed the FTIR spectra Organic and Medicinal Chemistry International Journal peaking at 3414.50cm -1 , 2929.63cm -1 , 2854.70cm -1 and 1453.40cm -1 corresponding to O-H stretching of alcohol, carboxylic acids and C-N stretching respectively. The FTIR spectroscopic analysis of n-hexane extract (Table 7) displayed absorption bands 3288.63cm -1 , 2993.83cm -1 , 1500.23cm -1 and 1057.85cm -1 respectively [24].…”
Section: Ftir Spectroscopysupporting
confidence: 86%
“…C-O stretching and aldehyde group respectively [50]. Similar results were previously reported by [51] which revealed the FTIR spectra Organic and Medicinal Chemistry International Journal peaking at 3414.50cm -1 , 2929.63cm -1 , 2854.70cm -1 and 1453.40cm -1 corresponding to O-H stretching of alcohol, carboxylic acids and C-N stretching respectively. The FTIR spectroscopic analysis of n-hexane extract (Table 7) displayed absorption bands 3288.63cm -1 , 2993.83cm -1 , 1500.23cm -1 and 1057.85cm -1 respectively [24].…”
Section: Ftir Spectroscopysupporting
confidence: 86%
“…and Shigella dysenteriae with MIC value ranged from 8-64 µg/ml against the tested bacterial pathogen [22] . Rai et al [23] reported antibacterial activity of the rhizome extract of A. rivularis against both gram-positive and gram-negative bacterial pathogens such as B. subtilis, Bacillus amyloliquefaciens, Aeromonas liquefaciens, Flexibactor sp., and Psedomonas sp. Adhikary et al [24] reported antimicrobial activity of rhizome methanolic extract of A. rivularis against E. coli with MIC of 0.011 mg/ml.…”
Section: Resultsmentioning
confidence: 99%
“…Plants have demonstrated their ability to inhibit the proliferation of several tumor cell lines over time due to their abundance of bioactive compounds, particularly flavonoids, terpenoids, and saponins, which have a potent cytotoxic effect [59,60]. These classes of secondary metabolites have already been identified in C. tougourensis [61].…”
Section: Cytotoxicity Predictionmentioning
confidence: 99%